2018
DOI: 10.21037/mhealth.2018.09.04
|View full text |Cite
|
Sign up to set email alerts
|

Stick To It: pilot study results of an intervention using gamification to increase HIV screening among young men who have sex with men in California

Abstract: Background: In the United States, young men who have sex with men (YMSM) experience a disproportionate burden of HIV and sexually transmitted infections (STIs). Mobile health (mHealth) interventions, including those that incorporate elements of games ("gamification"), have the potential to improve YMSM engagement in desirable sexual health services and behaviors. Gamification leverages theory and tools from behavioral science to motivate people to engage in a behavior in a context of fun. The objective of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Other studies reported retention rates of 70% to 90%. Two other studies reported notably higher rates of attrition than the others [ 65 , 89 ]. These high rates of attrition did not appear linked to acceptability, with both interventions reporting largely positive responses from participants.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Other studies reported retention rates of 70% to 90%. Two other studies reported notably higher rates of attrition than the others [ 65 , 89 ]. These high rates of attrition did not appear linked to acceptability, with both interventions reporting largely positive responses from participants.…”
Section: Resultsmentioning
confidence: 85%
“…The majority of the interventions identified in this review were targeted toward risk reduction or the management of STIs. Of the 17 interventions identified as having focused on risk reduction and management of STIs, 1 focused on pre-exposure prophylaxis adherence [ 66 ], 2 focused on reducing unprotected sex [ 67 - 71 ], 7 targeted multiple aspects of HIV prevention [ 72 - 83 ], 2 focused on HPV prevention [ 84 , 85 , 101 ], 3 focused on increasing STI testing [ 86 - 89 ], and 2 focused on antiretroviral medication adherence [ 90 , 91 ]. All 17 interventions were targeted toward young men who are attracted to men, 2 of which were specifically for adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, a strength of the online approach to implementation is that it allowed participants to complete the post-test survey independently, separate from researchers and healthcare providers, potentially limiting the impact of social desirability on our findings. Relatedly, a recent HIV prevention study with YMSM found that levels of study engagement were similar among participants recruited online and those recruited via their clinic (29). Future research using an online approach, yet drawing from a broader geographic range, and from both urban and rural settings, seems warranted.…”
Section: Discussionmentioning
confidence: 97%
“…Sandra I. McCoy from the University of California, Berkeley School of Public Health and her team recently developed an innovative mHealth intervention using gamification (the use of game elements in non-game setting). The intervention, Stick To It, aims to motivate young men who have sex with men (YMSM) to engage in desirable sexual behaviors in a context of fun and ultimately increasing repeat HIV screening (2). In the following interview with Prof. McCoy, mHealth will invite you to have a closer look at her research in this regard.…”
mentioning
confidence: 99%